Flavonoid Compounds from Ethanol Extract of Sungkai Leaves (Peronema canescens. Jack) and Antibacterial Activity Test Against Staphylococcus epidermidis and Escherchia coli - Susanto, Nindita Clourisa Amaris; Ardhica, Jammes; Nelson; Latief, Madyawati (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2022)
The rise of antibiotic-resistant bacteria has intensified the global search for alternative antimicrobial agents, particularly from natural sources. Traditional medicinal plants have been widely recognized for their therapeutic potential, and Peronema canescens Jack is well-known to contain bioactive compounds. Among its pharmacological properties, its antibacterial potential has drawn scientific interest. Secondary metabolites such as flavonoids, tannins, and phenolics are believed to contribute to its antimicrobial activity. However, the specific antibacterial compounds in P. canescens remain largely unidentified. This study seeks to isolate and characterize antibacterial compounds from the ethanol extract of Sungkai leaves, aiming to discover new natural antibacterial agents. The research objectives include isolating antibacterial compounds using maceration extraction and fractionation, conducting phytochemical screening to identify metabolite classes, assessing antibacterial activity using the paper disc diffusion method, and characterizing bioactive isolates through UV-Vis spectrophotometry and FTIR analysis. The results indicate that the ethyl acetate fraction of the ethanol extract of P. canescens leaves exhibits significant antibacterial activity, particularly at concentrations of 500 and 1000 ppm. UV-Vis spectrophotometric analysis identified flavonoid compounds, including apigenin, flavones, and flavonols, based on characteristic absorption peaks. FTIR analysis confirmed the presence of functional groups associated with flavonoids, supporting their antibacterial potential. These findings highlight P. canescens as a promising source of natural antibacterial agents. Further studies focusing on compound purification and in vivo antibacterial testing are recommended to explore its pharmaceutical applications.